Theoretical and Experimental Study of Aluminum Foils and Paraffin Wax Mixtures as Thermal Energy Storage Material - Reyes-Salinas, A; Sepulveda-Palma, F; Henriquez-Vargas, L (Elsevier Ltd, 2017)
This study analyzes the effect of increased thermal conductivity in energy storage, using paraffin wax with 8% w/w of aluminum foils, obtained from waste materials. Three configurations previously not published of the aluminum foil were tested: stripes, horizontal perforated disks and vertical perforated foils. The aluminum foils doubled the thermal conductivity, achieving values of 0.63 W/mK, without significant statistical influence of the metallic configuration inside this material. Solidification time depended on the configuration of the aluminum foils, where differences of up to 38% were detected between horizontal perforated disks and stripes. The equations for the solidification process were numerically solved in Matlab using the finite volume method, finding good agreement for the simulated output air temperature when compared with experimental values (relative error <10 %). Later, a thermal energy accumulator was designed and assessed, which consisted of 12 cans with paraffin wax, using the horizontal perforated disks configuration. The energy stored by the phase change material was removed with air velocities between 0.5 − 1.5 m/s, reaching efficiencies close to 90% for the maximum air velocity. © 2016 Elsevier Ltd
Keywords: Energy storage; Phase change materials; Thermal conductivity